2011
DOI: 10.1186/1472-6831-11-23
|View full text |Cite
|
Sign up to set email alerts
|

Do public health nurses in Norway promote information on oral health?

Abstract: Background(i) to describe oral health counselling in Norway to parents with infants and toddlers, ii) to assess existing collaboration and routines in oral health matters between nurses and personnel in the PDS, iii) to evaluate to what extent oral health was integrated in the basic educational curriculum of public health nurses.MethodsThis study was based on two separate surveys: the sample of Study I was 98 randomly selected child health clinics. A questionnaire covering oral health promotion counselling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
1
20
1
7
Order By: Relevance
“…Mothers, being the child's primary care giver should be adequately exposed to oral health care issues which will be ultimately transferred to the child. Parental behavioral factors determine the oral health status of their children [6] and therefore they should be adequately educated on prevention of oral diseases. This should be done during the first two years of the child's life, which is the most important period [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers, being the child's primary care giver should be adequately exposed to oral health care issues which will be ultimately transferred to the child. Parental behavioral factors determine the oral health status of their children [6] and therefore they should be adequately educated on prevention of oral diseases. This should be done during the first two years of the child's life, which is the most important period [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation has already been made that professional nurses acquire basic oral health competencies so that they can provide preventive care for underserved populations. 26 Norwegian public health nurses already promote oral health, 27 and other medical professionals (pediatricians, primary health care providers, nurses) can also be trained to provide preventive dental care, including dental screening and referrals. 28 Canadian dentists can also contribute, by following the American Dental Association's recommendation to hold and promote community events, during which underserved children from low-income families receive free dental screenings, treatment and education.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results from another investigation among the Chief Dental Officers in Norway that reported an established cooperation between the PDS and the child welfare centres in almost all counties and with institutions for elderly in all counties . In spite of the established interprofessional cooperation, a study on public health nurses and promotion of oral health concluded that collaboration between child welfare centres and the PDS can be improved . Only half of the public health nurses claimed to have regular contact with the PDS, and a quarter felt their knowledge about oral health was insufficient.…”
Section: Discussionmentioning
confidence: 99%